القوة وأهميتها في العلاقات الدولية - ميليش, فريد (Latakia University Journal - Economic and Legal Sciences Series, 2016)
إن الأحداث والتطورات والمتغيرات الدولية ترتكز إلى المسارات التي تنحرف دائماً باتجاه ما نتيجة صراع الإرادات بين القوى والدول, بمعنى أن الأزمات السياسية التي تصيب الدول تعني مجموعة من التفاعلات بين قوى تعيش حالة صراع قد يبلغ درجة المواجهة, فلابد من قراءة المتغيرات السياسية، والاقتصادية وفق مناهج وأصول علمية لفهم ما يهدد المصالح العليا للدول، فالكثير من الأزمات المتعاقبة عبر التاريخ نتجت عن استخدام القوة المرتكزة إلى المعطى الموضوعي للموارد المتاحة, فتكون القوة هي الممارسة العملية والتوظيف السياسي في النطاق الخارجي من خلال الدبلوماسية أوالحرب بحيث تحدد الدولة على أساسها أهدافها، وتقرر الاختيار بين هذه الأداة أو تلك من أدوات القوة. لكي تكون الدول والقوى محركاً لفعاليات الوحدات السياسية في إطار المجتمع الدولي فقد سعت لامتلاك القوة الشاملة, وهناك دول تسخر الحروب الموضوعة في أجنداتها مسبقاً لتحقيق أهداف سياستها,و لا زالت الحرب أداة اساسية لدى الدول والحكومات والمجموعات لتحقيق مصالحها بالصراع المباشر,أو عبر التهديد بالعقوبات, أو الاستمالة بالمساعدات بما يسمى القوة الناعمة, وأحيانا بصيغة الشرعية الدولية بما في ذلك ظهور مصطلح محاربة الإرهاب وما رافقه من تغيرات عالمية أدى إلى دوران الشعوب في فلك الدول القوية سياسياً وعسكرياً واقتصادياً وتكنولوجياً. The events, the developments and the international changes are based on the tracks that always deviate as the result of wills struggle between the forces and states. In the sense that the political crises that countries face means a set of interactions among the forces that have conflict which may reach to a confrontation. So we must be aware of the political and economic changes, according to the scientific methods to understand what threatens the interests of the states. Many of the sequential crises throughout history are resulted from the use of the power which is based on the object of the available resources. Therefore, the power is the practical exercise and the political investment abroad and that happens through diplomacy or war so that the state can determine its objectives, and decide what to choose among those of power tools. The forces and the states have seek to own the overall power in order to be the motivator of the political units within the framework of the international community. There are countries which benefit from the wars set in their agendas in advance to achieve the aims of their policy. War is still an essential tool for states, governments and groups to achieve their interests through direct conflict, or through the threat of sanctions, or through aids, including the so-called soft power, and sometimes through the form of international legitimacy, including the emergence of the term "fighting terrorism" and what accompanied it of global changes led to politically, militarily, economically and technologically submission to the powerful nations.